2016
DOI: 10.12659/msm.901040
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and Prognostic Factors in 106 Prostate Cancer Patients Aged ≤55 Years: A Single-Center Study in China

Abstract: BackgroundEarly-onset prostate cancer patients (aged ≤55 years) from Western countries have been well characterized in previous studies. However, the clinicopathological and prognostic characteristics of early-onset Chinese prostate cancer patients have not yet been assessed. This study aimed to examine the clinicopathological and prognostic factors of prostate cancer patients aged ≤55 years in a single Chinese center.Material/MethodsOne hundred six prostate cancer patients aged ≤55 years with complete clinico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…It is well known that patients with prostate cancer in Asian countries present with more aggressive pathologic features, compared to Western men [ 24 , 25 ]. Especially for Korean patients, prostate cancer in Korean men is known to be more aggressive and exhibit poorer differentiation, regardless of the initial serum PSA level or clinical stage at presentation, than that of Western men [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that patients with prostate cancer in Asian countries present with more aggressive pathologic features, compared to Western men [ 24 , 25 ]. Especially for Korean patients, prostate cancer in Korean men is known to be more aggressive and exhibit poorer differentiation, regardless of the initial serum PSA level or clinical stage at presentation, than that of Western men [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The new GG system was validated in two large cohorts (men treated with radical prostatectomy (RP) or radiation), and both studies discovered that GGs predicted the risk of recurrence following the primary treatment [1,2]. In the larger study, the five-year biochemical recurrence (BCR)-free progression probabilities after RP for GGs 1 through 5 were 96% (95% confidence interval (CI), 95-96), 88% (95% CI, 85-89), 63% (95% CI, 61-65), 48% (95% CI, 44-52), and 26% (95% CI, [23][24][25][26][27][28][29][30], respectively [1]. Other studies also supported the validity of this new system [3,4].…”
Section: Introductionmentioning
confidence: 93%
“…Huang et al 19 compared the pathological characteristics and prognosis of patients with PCa in Taipei, between young and old age groups, and reported that patients with PCa aged < 50 years showed similar tumour grades, stages, PSA values, overall survival (OS), and BFSs to the older aged group. The Chinese study of Xu et al 8 reported that patients with PCa aged < 55 years are more likely to be diagnosed at an advanced stage, and their pathologic patterns were mostly complicated and associated with a high degree of malignancy. They demonstrated that the five-year OS of their younger group was significantly lower than that of European and American populations.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that patients with PCa in Asian countries present with more aggressive pathologic features, compared with Western men. 8 9 Man et al 9 reported that a greater proportion of Asian people had a high risk PCa compared with non-Asian men. The percentage of PCa with GS ≥ 8 was twice as high in Asian patients than in non-Asians at presentation (26.5% vs. 13.8%, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation